Diagnostic sensitivity and specificity of dynamic three-dimensional CT analysis in detection of cam and pincer type femoroacetabular impingement - Maarten A. Röling; Nina M. C. Mathijssen; Rolf M. Bloem (BMC Musculoskeletal Disorders, 2020)
Abstract Background Cam and pincer-type morphologies can cause femoroacetabular impingement syndrome (FAI) and can be measured on plain radiographs using the alpha angle and the center edge angle. As an addition to plain radiographs and to assess femoroacetabular impingement, it is possible to visualize the interplay of the acetabular and femoral morphology by means of dynamic three-dimensional simulation of hip joint. Therefore, the objective of this study is to compare alpha angles and center edge angles on plain radiographs with the dynamic computerized tomography (CT) analysis in patients with complaints of femoroacetabular impingement. Methods All patients from our prospective cohort from 2012 to 2015 who underwent radiographs and a dynamic CT analysis for FAI were selected. Cam type morphologies were measured with the alpha angle and pincer type morphologies with lateral center-edge angle on radiographs and with CT analysis. The dynamic CT analysis also calculated position and size of impingement of femur and acetabulum. Intra-operative assessment was used to confirm impingement. Sensitivity, specificity and predictive values were calculated compared with respect to the intra-operative assessment. Results A total of 127 patients were included. 90 cam morphologies and 45 pincer morphologies were identified intra-operatively. The sensitivity and specificity for cam morphology measured with radiographs was 84 and 72% compared to 90 and 43% with three dimensional dynamic analyses. The sensitivity and specificity for pincer morphology measured with radiographs was 82 and 39% compared to 84 and 51% with three dimensional dynamic analyses. Conclusions Diagnostic accuracy is comparable in three-dimensional dynamic analysis of CT scans and radiographs representing FAI caused by cam or pincer type morphology. Level of evidence IV